1998
DOI: 10.3109/08860229809045169
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in acute renal failure of septic origin: A multivariate analysis

Abstract: The goal of the present study was to identify variables associated with the outcome of patients with acute renal failure (ARF) of septic origin, using multivariate analysis. The records of 168 patients were reviewed retrospectively and a crude mortality of 74% was found. Both univariate as well as multivariate analysis demonstrated an association between mortality and variables which depended on patient related factors. These included age over 60 years and several underlying diseases such as pneumonia, periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
3
8
0
2
Order By: Relevance
“…In addition, the proportional, estimated survival in ARF patients, compared to non-ARF patients, was reduced throughout the first 30 days. The 43 % ICU mortality rate of ARF patients in our study population is comparable to recent values quoted in the literature [3,4,5,6,7,8,10,11,12]. In the present study, mortality was 3 times higher in those with, than in those without, ARF.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, the proportional, estimated survival in ARF patients, compared to non-ARF patients, was reduced throughout the first 30 days. The 43 % ICU mortality rate of ARF patients in our study population is comparable to recent values quoted in the literature [3,4,5,6,7,8,10,11,12]. In the present study, mortality was 3 times higher in those with, than in those without, ARF.…”
Section: Discussionsupporting
confidence: 79%
“…We believe that the combination of these two aspects is important, as oliguria may precede a rise in creatinine concentration. As in other studies [5,6,8,10,13], oliguria was an important prognostic factor; it independently doubled the risk of death for the entire population.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Esta observación es de vital importancia si se tiene en cuenta que la falla renal aguda es una de la principales causas de mortalidad en los pacientes con procesos infecciosos graves (75,76) y que su lesión durante la sepsis, generada por una serie de factores como la hipovolemia y la hipotensión, es un fenómeno común (77) y potencialmente reversible (49).…”
Section: Leucocitosunclassified
“…In a multivariate analysis, it has been found that three variables affect the result. These are; age over 60, pulmonary failure and hemodynamic failure (51). Especially, co-presence of pulmonary and renal failures is one of the most important factors threatening life.…”
Section: Early Antibiotic Therapy and Control Of The Source Of The Inmentioning
confidence: 99%